Intravitreal Kinetics of Hesperidin, Hesperetin and Hesperidin G: Effect of Dose and Physicochemical Properties - Srirangam, Ramesh (2012)
Hesperidin, a flavanone glycoside, and its aglycone hesperetin, are potential candidates for the treatment of diabetic retinopathy and macular edema. The objective of this study was to delineate the vitreal pharmacokinetics of hesperidin and hesperetin and the hydrophilic derivative hesperidin G (glucosyl hesperedin), following intravitreal administration in anaesthetized rabbits. Concentration changes in the vitreous humor were monitored using microdialysis sampling procedure. All three molecules were administered intravitreally at three dose levels (50 μl injection volume containing 1.5, 4.5 and 15 µg of the drug, resulting in a final vitreal concentration of 1, 3 and 10 μg/mL). Vitreal microdialysis samples were collected every 20 minutes over a period of 10 h. All three molecules exhibited linear pharmacokinetics, within the dose range tested, since AUC and Cmax increased linearly with increasing dose and a significant difference in the elimination parameters, like clearance or half-life, was not observed. The vitreal elimination half-life of these three compounds was observed to correlate with the molecular weight and lipophilicity of the molecules. The findings from this study provide practical information that will be useful in the future design of ocular drug delivery strategies for the bioflavonoids.